2018
DOI: 10.1007/s00432-018-2802-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of VEGFR1+ hematopoietic progenitor cells on pre-metastatic niche formation and in vivo metastasis of breast cancer cells

Abstract: The pre-metastatic niche has been shown to play a critical role in tumor metastasis, and its formation is closely related to the tumor microenvironment. However, the underlying molecular mechanisms remain unclear. In the present study, we successfully established a mouse model of lung metastasis using luciferase-expressing MDA-MB-435s cells. In this model, recruitment of vascular endothelial growth factor receptor-1 (VEGFR1) + CD133 + hematopoietic progenitor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…Six weeks after inoculation of 4 T1 cells, HSPCs were found to appear a sharp decrease. This was consistent with the findings of Liu et al that HSPCs population was gradually decreased after the formation of tumor colonies in target organs of metastasis [19]. Moreover, TAMs co-inoculation was found to promote HSPCs recruitment and MDSCs differentiation, which was blocked by XIAOPI formula and CXCL1 knockdown.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Six weeks after inoculation of 4 T1 cells, HSPCs were found to appear a sharp decrease. This was consistent with the findings of Liu et al that HSPCs population was gradually decreased after the formation of tumor colonies in target organs of metastasis [19]. Moreover, TAMs co-inoculation was found to promote HSPCs recruitment and MDSCs differentiation, which was blocked by XIAOPI formula and CXCL1 knockdown.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies suggested that PMN formation is a critical factor determining the site and time of cancer metastasis [19,20]. Drugs targeting PMN could represent a novel therapeutic strategy in improving clinical outcomes of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic portal vein injection was used to inoculate HCC cells into the liver of nude mice, simulating the recurrence or metastasis of HCC cells in patients. In addition Meng et al [70][71][72] established a research model for the invasion of malignant tumor cells in the liver of nude mice. Li et al 73 developed a breast cancer lung metastasis model in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs found in the TME can come from platelets or platelet microparticles (PMPs). PMPs are the most abundant microparticles in the blood and contain, in addition to miRNAs[ 53 ], several EMT-promoting factors, including basic fibroblast growth factor (bFGF), fibroblast growth factor (FGF)[ 54 ], platelet-derived growth factor (PDGF)[ 55 ], hepatocyte growth factor (HGF)[ 56 ], TGF-β[ 57 ], vascular endothelial growth factor (VEGF)[ 58 ] and brain-derived neurotrophic factor/tropomyosin-related kinase (BDNF/TRK)[ 59 ].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%